The Ethics of War and Peace in Russian Philosophy and the Ethical Consequences of Modern Legal Precedents on Warfare and Armed Forces - Minchenko, Tatiana (Conatus - Journal of Philosophy, 2024)
The first part of the study is devoted to a comparative analysis of the concepts of the Ethics of War and Peace in Russian philosophy and its influence on the world practice of nonviolence. The second part of the study is devoted to analyzing the impact of changes in legislation and law enforcement practice on the moral state of society concerning the Armed Forces and military operations after the collapse of the USSR. In conclusion, a summary of the research is given. The relevance of the ideas of Russian thinkers about the need for a clear definition of the concepts with which we describe reality, the relevance of non-violent conflict resolution, the priority of preserving and developing human-oriented culture, law and morality for the formation of a healthy society with the conditions of the Noosphere are drawn.